EDUKASI STIMULASI PERKEMBANGAN BADUTA DENGAN MEDIA VIDEO ANIMASI DI POSYANDU KUNCUP MEKAR 1 DESA SIKASUR - Putri, Adinda Yulia; Triana, Noor Yunida; Wirakhmi , Ikit Netra (LPPM Universitas Flores, 2024)
The development of children aged 0-24 months is crucial for the child's survival. One effort to maintain children's growth within the normal range is by providing stimulation to children. This service aims to identify the characteristics of respondents (age, education and occupation), provide health education and identify the mother's level of knowledge before and after health education. Sampling was done using lecture, discussion, question and answer, and demonstration methods, totalling 19 respondents, namely mothers with babies aged 0-24 months. The research instrument uses a pre-test and post-test questionnaire. The media used are powerpoint, animation videos, and pocket books. The results obtained were that the characteristics of the participants were that most of them were aged 20-35 years (69%), some of the participants had completed elementary school education (58%) and most of the participants worked as housewives (89%). There is a difference before and after health education, namely an increase in pre-test and post-test results, as evidenced by the average pre-test score of 60.94 in the sufficient category, and the average post-test score of 75.47 in the good category. This shows increased maternal knowledge before and after health education, namely 14.53. It is hoped that the implementation of Community Service (PkM) can continue health education activities regarding stimulating development by adding personnel who aim to assist in the service process to make it more efficient. Apart from that, door prizes are made as attractive as possible so that participants are interested in participating.